The role of foreign language anxiety on L2 utterance fluency during a final exam. (July 2019) - Pérez Castillejo, Susana
This study examines how foreign language anxiety (FLA) and proficiency relate to second language (L2) utterance fluency during a final oral exam. Thirty-eight learners of Spanish (L1 English) completed unplanned narratives that were coded for ratio and length of pauses between and within Analysis of Speech Units, mean length of run, phonation-time ratio, and articulation rate. Learners' oral proficiency was measured with an aural/oral sentence imitation task. Multiple regression analyses showed that anxiety is a strong predictor for certain temporal features associated with subjective ratings of fluency. Overall oral proficiency, however, was not a significant predictor in any case. The findings confirm the interference of FLA with cognitive processing and contribute to our understanding of the challenges faced by anxious learners during classroom-based language assessment.